2010
DOI: 10.1017/s0954422410000223
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of edible oils: a comparison between four popular edible oils

Abstract: Edible oils form an essential part of the modern diet. These oils play a role as an energy source, and provide the diet with many beneficial micronutrients. Although a popular conception may be that fat should be avoided, certain edible oils as a dietary supplement may play an important role in the improvement of cardiovascular health. CVD has become one of the leading causes of death worldwide. Dietary supplementation with different oils may have beneficial effects on cardiovascular health. While olive oil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 120 publications
0
44
0
5
Order By: Relevance
“…A comprehensive review by Granados‐Principal and others (2010) states that the antioxidative olive compound 4‐hydroxytyrosol contributes to many health‐promoting effects ascribed to the consumption of olive oil (Cornwell and Ma 2008; Cicerale and others 2010; González‐Santiago and others 2010). These include anticancer (Hashim and others 2005; Corona and others 2009), antiaging (Jacomelli and others 2010), anticholesterol (Fki and others 2007; Jemai and others 2008), antidiabetic (Hamden and others 2009; Jemai and others 2009), anti‐inflammatory (suggesting control of proinflammatory genes) (Zhang and others 2009b), antimicrobial (Medina and others 2007; Serra and others 2008; Moore and others 2011), antiviral (Yamada and others 2009), adverse cardiovascular effects (Bester and others 2010), prevention of bone loss (Hagiwara and others 2011), protection of oxidative injury of kidney cells (Incani and others 2010), suppression of oxidative stress (Zhu and others 2010), and protection against acrylamide induced cytotoxicity and DNA damage in HepPG2 cells (Zhang and others 2009a). Inhibition of proliferation of human colon adenocarcinoma cells by 4‐hydroxytyrosol may explain the inverse relationship between colon cancer and consumption of olive oil (Corona and others 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive review by Granados‐Principal and others (2010) states that the antioxidative olive compound 4‐hydroxytyrosol contributes to many health‐promoting effects ascribed to the consumption of olive oil (Cornwell and Ma 2008; Cicerale and others 2010; González‐Santiago and others 2010). These include anticancer (Hashim and others 2005; Corona and others 2009), antiaging (Jacomelli and others 2010), anticholesterol (Fki and others 2007; Jemai and others 2008), antidiabetic (Hamden and others 2009; Jemai and others 2009), anti‐inflammatory (suggesting control of proinflammatory genes) (Zhang and others 2009b), antimicrobial (Medina and others 2007; Serra and others 2008; Moore and others 2011), antiviral (Yamada and others 2009), adverse cardiovascular effects (Bester and others 2010), prevention of bone loss (Hagiwara and others 2011), protection of oxidative injury of kidney cells (Incani and others 2010), suppression of oxidative stress (Zhu and others 2010), and protection against acrylamide induced cytotoxicity and DNA damage in HepPG2 cells (Zhang and others 2009a). Inhibition of proliferation of human colon adenocarcinoma cells by 4‐hydroxytyrosol may explain the inverse relationship between colon cancer and consumption of olive oil (Corona and others 2009).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, sunflower oil has shown few effects on the cardiovascular system, apart from its beneficial effect on the serum lipid profile (5). …”
Section: Discussionmentioning
confidence: 99%
“…It is a mixture of oleic acid and stearic acid as major monounsaturated fatty acids (MUFA) and SFA, respectively (5). …”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids maintained a similar percentage increase (4, 2, and 0%) in the MCao, MCas, and MCac groups, with respect to the SG group, and showed no significant effect on this indicator; however, their levels were all significantly higher, by 33, 30, and 28%, respectively, in relation to the CG group. Other researchers have reported that, although olive oil has a hypocholesterolemic effect on the serum lipid profile [28], there is some evidence to suggest that it does not significantly affect the profile of heart or erythrocyte phospholipids [29]. On the other hand, it has been found that avocado oil supplementation in rats increases the phospholipid fraction in HDL as a surface component [30]; the present study shows that avocado oil, while being a crude oil high in micronutrients, also has a significant percentage of monounsaturated fatty acids (18:1N9 oleic: 54–59%), which could explain its effect to increase phospholipid levels.…”
Section: Discussionmentioning
confidence: 99%